Model Pendidikan Di Pesantren Rakyat Al-Amin Sumberpucung Malang - Jumain, Jumain (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
System is a set of elements of education which are related and connectedÂ each other and give influence each other to achieve a certain goal. OneÂ of attempt that can be done is through developing system of IslamicÂ Education there, while the model is a product of developing system.Â Focus of this research is how the model of â€œRakyat Al Aminâ€ IslamicÂ boarding school in SumberpucungKab. Malang including some componentsÂ of Islamic boarding school itself: boarding, mosque, Islamic classic books,Â students and kiyai. This research used study case and Analyzing datadone through two steps, the first step is step with the process of collectingÂ data in the field and step after collecting data.Â The result of this research shows the difference of the components ofÂ Islamic boarding school commonly and the components of Rakyat IslamicÂ boarding school. In the reality Rakyat Islamic boarding school only has 3Â components such as teaching Islamic classic book, students and kyai, butÂ it doesnâ€™t mean that the other components of Islamic boarding school areÂ not important, the other components just have different function.Key word: Model of Islamic Boarding School